Geopolitical risks for Egypt wheat supply and trade - Gebeltová, Zdeňka; Hálová, Pavlína; Malec, Karel; Bartoňová, Klára; Blažek, Vojtěch; Maitah, Mansoor; Koželský, Robert; Phiri, Joseph; Appiah-Kubi, Seth Nana Kwame; Tomšík, Karel; Severová, Lucie; Marušiak, Jiŕí (Frontiers in Sustainable Food Systems, 2023)
Introduction Since 2005, Russia has established a stable position in Egypt's wheat imports, and after 2016, it became the largest global wheat exporter. The shift in Russian grain production has visibly affected wheat export destinations in favor of developing countries. This paper identifies the main determinants of wheat trade in Egypt concerning the primary risks associated with the war in Ukraine. Methods The paper utilizes time series analysis, index analysis, and an econometric model to define the statistical relationship between the quantity of wheat imported into Egypt and population development, wheat price, and wheat production. Results Despite increasing wheat production growth rates (1.9% p.a. over 2000–2020) and a growing population (2.01% p.a.), Egypt is unable to reduce its import dependence below 50% of total consumption. Undernourishment in Egypt remains at 5.2%–5.4% of the population. The econometric model shows that variables describing the evolution of production, population, and prices are statistically significant in relation to wheat imports. Egypt's wheat imports continue to increase even with rising prices, which is typical for developing countries. The war in Ukraine and associated commodity price increases have far-reaching implications for Africa's food security and supply systems. Discussion Egypt's vulnerability to external influences, such as climate change, migration, rising commodity prices, and population growth, exacerbates the situation. Most African countries, including Egypt, struggle with the economic and social impacts of the COVID-19 pandemic. They also face rising food and energy prices, conflicts between the world's largest food producers, and increasing poverty rates. The research findings confirm that Egypt is among the highly vulnerable countries due to the war in Ukraine and the disruption of agricultural supply chains.